Penerapan Kompres Serai Hangat Sebagai Manajemen Nyeri pada Pasien dengan Osteoarthritis di RS Jakarta Barat - Ratih Widiastri; Dewi Retno Puspitosari; Rizki Bahtiyar; Edi Santoso (Lembaga Pengembangan Kinerja Dosen, 2026)
Osteoarthritis (OA) is a disease that occurs due to damage to the cartilage tissue that lines the bones, causing the bones to rub against each other during movement. One nursing action to address pain in OA patients is to provide warm lemongrass compresses. This case report aims to determine the effectiveness of applying warm lemongrass compresses in reducing pain levels in osteoarthritis patients. The method used is a case study on OA patients experiencing discomfort due to pain. Warm lemongrass compresses were given three times a day for three days. The instrument used was the Numeric Rating Scale (NRS) to measure pain levels. The results of this report show that warm lemongrass compresses for three days successfully reduced pain levels significantly, from a scale of 6 to a scale of 3. Warm lemongrass compresses have been proven to be an effective non-pharmacological therapy in standard nursing care interventions to reduce pain levels in osteoarthritis patients. This intervention can be an additional therapeutic option in the management of OA pain.